Leadership and Organisational Success in Nigeria: A Study of The Delta State University, Abraka - OKEREKA, Onofere Princewill; DENEDO, Emuobonuvie Nathaniel (Management Research and Behavior Journal, 2024)
The study examined leadership and organisational success in Nigeria using Delta State University, Abraka as a case study. The study adopted across-sectional research design and data was collected via a survey of 400 respondents in Delta State University using purposive sampling. Data collected were analysed using Pearson's product moment correlation analysis with the aid of statistical package for Social Science (SPSS) version 23 and the hypotheses were tested at the 0.05 levels of significance. The result of the study showed that transformational leadership positively enhance organisational commitment of employees in other achieve goals in an organisations, time prioritization positively and significantly influenced employee productivity in selected local government councils and leadership positively and significantly enhance organisational behaviour and commitment in an organisation in Delta State university Abraka, Nigeria. This study concluded that leadership influence organisational success in Nigeria and suggested among others that in order for leaders to address the needs, demands, concerns, and issues of an organisation, they should uphold high moral standards and an ethical code of conduct.